E-COMMERCE UTILIZATION MANAGEMENT AS PROMOTIONAL TOOL FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN BANDA ACEH - Syahril Furqany (Al-Idarah: Jurnal Manajemen dan Administrasi Islam, 2020)
Advances in communication technology must be beneficial for entrepreneurs, especially small and medium entrepreneurs. If you want more advanced businesses, then local entrepreneurs in Banda Aceh must be pro to technological advancements. The purpose of this study is to obtain data related to small businesses in Banda Aceh in utilizing e-commerce as a promotional medium. As a tool to capture consumers in an unlimited number. This study uses qualitative data as many as 50 respondents of small and medium businesses in Banda Aceh. Qualitative data is used to present comprehensive data on the use of e-commerce as a medium for promotion of small and medium businesses. The results of the study indicate that there is still a need for assistance to small and medium businesses in the effort to utilize e-commerce. What makes a good and interesting message with the aim of being a stimulus for consumers. Several medium-sized businesses have increased promotion through e-commerce. By creating their own brand, attractive packaging, the next complexity is how the product is marketed to the public. Constraints that are sold do not have a clear product marketing strategy. Currently only selling directly by attending the exhibition stands. Has not implemented a reseller system, due to budget and employee limitations. Need for supplies related to promotion through resellers.